Ensuring safety of living and psychology of negative relations in society as interpreted by the tatar folk pedagogy (on the example of proverbs and sayings) - Rustam Shaydullovich Malikov; Igor Nikolaevich Fedekin; Firuza Vakilovna Khazratova; Liliya Ravilevna Sadykova; Farida Samigullovna Gazizova (Вестник Майкопского государственного технологического университета, 2023)
The relevance of the research consists in the fact that the folk wisdom of any nation contains morals for all occasions. Scientific researches usually consider only positive examples of educational value, despite the fact that folk wisdom contains thoughts that warn of danger. The problem is that it is necessary to uncover the thoughts of the Tatar people about ensuring life safety in everyday conditions, in particular in relations with a neighbor. The Tatar people are versatile and diverse in revealing and describing relations and interactions with their neighbors. Tatar folk proverbs and sayings contain more thoughts about a positive attitude towards a neighbor than careful handling of them. The purpose of this study is to reveal folk wisdom from the point of view of ensuring life safety at the household level. Empirical methods such as observation, comparing proverbs and sayings with the experience of people in real life, and theoretical methods such as abstraction, analysis and synthesis, idealization, induction and deduction, mental modeling, ascent from the abstract to the concrete, etc. have been used in the research. As a result, the authors have revealed that Tatar Folk Pedagogy, in particular, proverbs and sayings contain many examples of how to properly organize relations with neighbors, to keep distance, to be compliant, to live in harmony and peace, to know the recommendations and adhere to the instructions of Folk Pedagogy, so that one doesn’t run into trouble. All this in the end will preserve the life and health of people, it’s something everyone should know about, because everyone has beloved neighbors. Key findings: examples from the Tatar Folk Pedagogy are offered to students at pedagogical universities in History of Pedagogy, Psychology, Theory and methods of educational work, and Life safety classes in the area of preparation of 4.03.01 “Pedagogical education”.